Impact of Catheter Contact Force on Human Left Atrial Electrogram Characteristics in Sinus Rhythm and Atrial Fibrillation. (October 2015) - Ullah, Waqas; Hunter, Ross J.; Baker, Victoria; Ling, Liang-Han; Dhinoja, Mehul B.; Sporton, Simon; Earley, Mark J.; Schilling, Richard J.
Abstract : Background—: During left atrial mapping, optimal contact parameters minimizing variation secondary to catheter contact are not established. Methods and Results—: Across 30 patients undergoing first-time atrial fibrillation ablation, 1965 stable mapping points (1409 atrial fibrillation, 556 sinus rhythm), comprising 8-s contact force (CF) and bipolar electrogram data were analyzed. Points were taken in groups at locations with CF or catheter orientation actively changed between acquisitions. Complexes were less positive at higher CF (Spearman ρ, −0.2; P <0.005, both rhythms). Increasing CF at a location significantly increased complex size, but only where initial CF was <10 g, and if the change was ≥4.5 g in sinus rhythm and ≥8 g in atrial fibrillation ( P <0.0005, both rhythms): if initial CF was ≥10 g, no change was observed, regardless of CF change ( P >0.05, both). Atrial ectopics during sinus rhythm were observed more frequently when CF was ≥10 g ( P <0.0005). Increasing CF at a location was associated with an increase in the complex fractionated atrial electrogram interval confidence level score, but only if initial CF was <10 g and CF increased ≥8 g ( P =0.003). The dominant frequency and organization index were unaffected by CF ( P >0.1 for both). Changing catheter orientation from perpendicular to parallel in atrial fibrillation was associated with smaller, more positive complexes ( P =0.001 for both), but no changes in complex fractionated atrial electrogram scores, dominant frequency or organization index ( P >0.08 for each). Conclusions—: During left atrial electrogram mapping, including complex fractionated atrial electrogram but not spectral parameter mapping, CF and catheter orientation influence results: consequently, mapping CFs should be ≥10 g to negate the influence of CF. Clinical Trials Registration—: URL:http://clinicaltrials.gov/ . Unique identifier: NCT01587404.